Analisis Penerapan Akuntansi Lingkungan pada Rumah Sakit RS Islam Jakarta - Nani Jumanti (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Clean or healthy environment is a condition in which the surrounding environment is maintained cleanliness and does not endanger human health. Dirty environment can cause various diseases, such as respiratory diseases, skin infections, and waterborne diseases. The root cause of dirty environment is often associated with human behavior of littering and improper waste disposal. Waste and pollutants can cause various health problems. This research aims to determine whether this hospital has implemented environmental accounting properly. This study uses qualitative descriptive as the object is Islamic Hospital in Jakarta. This research involves staff from the Environmental Health department and the finance director. The results of this research show that Islamic Hospital Jakarta is very concerned about the surrounding environment as evidenced by the cost incurred for waste processing amounting to 30% of the total overhead costs and there are no external failure costs incurred by the hospital.